From an understanding of etiopathogenesis to novel therapies—what is new in the treatment of celiac disease? - Skoracka, Kinga; Hryhorowicz, Szymon; Tovoli, Francesco; Raiteri, Alberto; Rychter, Anna Maria; Słomski, Ryszard; Dobrowolska, Agnieszka; Granito, Alessandro; Krela-Kaźmierczak, Iwona (Frontiers in Pharmacology, 2024)
Celiac disease, a chronic autoimmune disorder caused by genetic factors and exposure to gluten, is increasingly being recognized and diagnosed in both children and adults.Scientists have been searching for a cure for this disease for many years, but despite the impressive development of knowledge in this field, a gluten-free diet remains the only recommended therapy for all patients. At the same time, the increasing diagnosis of celiac disease in adults, which was considered a childhood disease in the 20th century, has opened a discussion on the etiopathology of the disease, which is proven to be very complex and involves genetic, immunological, nutritional, environmental and gut microbiota-related factors. In this review, we extensively discuss these factors and summarize the knowledge of the proposed state-of-the-art treatments for celiac disease to address the question of whether a better understanding of the etiopathogenesis of celiac disease has opened new directions for therapy.